The Alphabet of Economic Science - Stigler, George J.; Wicksteed, Philip H. (Econometrica, 1956)
Vols 1 & 2: The Common Sense of Political Economy and Selected Papers and Reviews on Economic Theory, ed. Lionel Robbins (1933, 940pp). Vol 3: The Alphabet of Economic Science (1888, 160pp). Vol 4: An Essay on the Co-Ordination of the Laws of Distribution (1894, 60pp) Getting and Spending - Papers on the Meaning and Uses of Money (1888, rep.1897, 40pp). Vol 5: Philip Henry Wickstead - His Life and Work, C.H. Herford (1931, 446pp).